Self-reported hearing loss as an alternative hearing screening tool among adults: an introduction to Inventori Laporan Masalah Pendengaran (ILAMP) - Amir, Najihah; Rahmat, Sarah; Lamri, Marina L. Alisaputri @ Marina (Malaysian National Society of Audiologists, 2021)
An ongoing study by the authors focuses on developing a Malay self-reported hearing loss inventory for adults known as Inventori Laporan Masalah Pendengaran (ILaMP). The development of ILaMP was initiated due to the fact that there was no comprehensive self-reported hearing loss survey available in Malay. A pilot study of ILaMP on 90 subjects has been conducted. The initial analysis showed that ILaMP can differentiate between normal hearing and hearing loss subjects (p < 0.05). It has a good potential to be used as an alternative hearing screening tool due to its performance, easy administration, and cost- and time- efficiency.However, further investigation on the sensitivity, specificity, and accuracy of ILaMP needs to be conducted on a larger population.